Genotypic Variability in Architectural Development of Mungbean (Vigna radiata L.) Root Systems and Physiological Relationships With Shoot Growth Dynamics - Singh, Vijaya; Bell, Michael (Frontiers in Plant Science, 2021)
Selection for a root system architecture (RSA) to match target growing environments can improve yields through better adaptation to water and nutrient-limiting conditions in grain legume crops such as mungbean. Most studies on RSA have characterised root architectural parameters at a specific time, mostly at maturity. The lack of studies with destructive sampling over time limit the ability to determine interactions between RSA and plant growth and yield development. In this study, the architectural development of intact root systems in four contrasting mungbean genotypes was studied over time to explore their relationships to plant growth and development. Key findings suggested that early maturing mungbean genotypes were characterised by more rapid root elongation rates and leaf area development, resulting in more vigorous root and shoot growth during early growth stages compared with a late maturing genotype. The early maturing genotypes also showed root morphological traits generally adapted to water-limited environments, such as deeper, longer and lighter roots. The late maturing genotype exhibited relatively thicker roots in topsoil layers that could provide a better anchorage to support the relatively larger plants, while also enabling greater soil exploration and nutrient acquisition in surface soil layers. The latter trait would be particularly advantageous for acquiring immobile nutrients such as phosphorus. The diversity of root characteristics identified in these commercial varieties suggests there are opportunities to combine desirable root traits with maturity types to target different production environments. Examples include deeper, longer and thinner roots in early maturing genotypes, to allow time to exploit deep profile reserves of water and nutrients, and thicker and shallower root systems in late maturing genotypes grown in shallow soils with stratified nutrient reserves and/or more favourable in-season rainfall.